STRATEGIC INTELLIGENCE AND ITS ROLE IN SUPPORTING ORGANIZATIONAL RENEWAL - Ass. Prof. Jinan Mehdi Shaheed (Scholars Digest Publishing, 2024)
This study sought to determine the impact of strategic intelligence and its role in supporting organizational renewal. To achieve this, the study adopted the dimensions of strategic intelligence represented by (foresight and future vision). (systems thinking, motivation, partnership) and the dimensions of organizational renewal represented by (strategic capability, Communication, time investment, leadership practices, orientation towards learning, and knowledge management). The study population represented the University of Karbala, and the study variables were measured using a questionnaire. It was prepared for this purpose, as 85 questionnaires were distributed. The study reached a set of conclusions, the most important of which is the existence of a positive and robust influence relationship. It has a moral significance for strategic intelligence in supporting organizational renewal. The study has concluded with a set of recommendations, among the most important of these recommendations was enhancing awareness and awareness of the concept of intelligence. The strategy and its role in supporting and encouraging commitment among working individuals by pushing them to participate. In the processes of supporting organizational renewal.
Keywords: strategic intelligence, organizational renewal.